Assistance to Indonesian Sugarcane Farmers in Sleman Yogyakarta in Support of Increasing Crop Productivity and Strengthening Cooperatives - Anna Kusumawati; Azhari Rizal; Dwi Aryani Suryaningrum; Luci Paonganan; Muhamad Mustangin; Yunaidi Yunaidi; Ratna Sri Harjanti (PRIMA: Journal of Community Empowering and Services, 2023)
One of the pillars that will support the sugar self-sufficiency program proclaimed by the Indonesian government is smallholder sugarcane farmers. The problems faced are not only on-farm problems such as land management and inaccurate pest control, but also sugarcane farmer cooperatives which have many obstacles. This causes productivity both in terms of cultivation to be less than optimal and the existing cooperatives to be unable to run as originally intended. The purpose of this community service is to provide assistance to people's sugarcane farmers by providing counseling on good sugarcane management, proper sugarcane control, and cooperative management. This activity was carried out with partners from smallholder sugarcane farmers in Sleman who are members of the Koperasi Petani Tebu Rakyat Sido Makmur Abadi which is located at Jl. Raya Selomartani Dayakan, Purwomartani, Sleman. In Yogyakarta. The activity phase that has been carried out is preceded by coordination to discuss the main problems of sugar cane farmers, then there is socialization regarding alternative solutions to farmer problems, and finally assistance in the form of counseling. The results of the activities showed an increase in knowledge regarding good sugarcane cultivation techniques and proper beetle larvae control by 41% and regarding cooperative management by 60%. It is hoped that this increased understanding will become the basis for improving cultivation activities in the 2023-2024 sugarcane planting year so that productivity increases and sugarcane farmer cooperatives are better managed